2011
DOI: 10.1007/s11244-011-9746-2
|View full text |Cite
|
Sign up to set email alerts
|

Lean NO x Reduction with Various Bio-Diesels as Reducing Agents

Abstract: Commercial Cu-ZSM-5-and Ag/Al 2 O 3 -based lean NO x catalysts were evaluated in a synthetic exhaust gas bench with the fuels RME, B30, B15, Agrodiesel 15, GTL, NExBTL, and MK1 as reducing agents. The influence of reductant was larger for Ag/Al 2 O 3 , albeit moderate, whereas the Cu-zeolite showed the highest NO x conversion at lower temperature for all alternative fuels tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A previous study of the same catalysts with different biodiesels as reducing agents showed that the oxygenated fuel RME gave a lower maximum NO x conversion and at a higher temperature over the Ag/Al 2 O 3 catalyst than over Cu-ZSM-5 [6]. In general, Ag/Al 2 O 3 was there found active at a higher temperature and shown to be more sensitive to the fuel used as reducing agent than Cu-ZSM-5.…”
Section: Catalytic Activity With Triglyme As Reducing Agentmentioning
confidence: 80%
“…A previous study of the same catalysts with different biodiesels as reducing agents showed that the oxygenated fuel RME gave a lower maximum NO x conversion and at a higher temperature over the Ag/Al 2 O 3 catalyst than over Cu-ZSM-5 [6]. In general, Ag/Al 2 O 3 was there found active at a higher temperature and shown to be more sensitive to the fuel used as reducing agent than Cu-ZSM-5.…”
Section: Catalytic Activity With Triglyme As Reducing Agentmentioning
confidence: 80%